Chemotherapy combined with regorafenib and immune checkpoint inhibitors as a first-line treatment for patients with advanced biliary tract cancer: a single arm phase II trial - Liu, Jianwei; Bai, Shilei; Sun, Yanfu; Hu, Lei; Ge, Ruiliang; Xue, Feng (Frontiers in Immunology, 2024)
Objective: This study aimed to investigate the efficacy, long-term prognosis and safety of combining chemotherapy with regorafenib and immune checkpoint inhibitors as first-line treatment for patients with advanced biliary tract carcinoma (BTC).In this single arm phase II trial, twenty-nine patients with advanced BTC were included, all of whom received gemcitabine-based chemotherapy combined with regorafenib and immune checkpoint inhibitors as the first-line treatment. And the study analyzed anti-tumor efficacy, long-term prognosis, and adverse reactions.Results: Among the patients, 0 patient achieved complete response, 18 patients (62.1%) achieved partial response, 8 patients (27.6%) had stable disease, and 3 patients (10.3%) experienced progressive disease. The corresponding objective response rate (ORR) was 18/29 (62.1%), and the disease control rate (DCR) was 26/29 (89.7%). The median overall survival (OS) was 16.9 months (95% confidence interval [CI]: 12.0 -21.8) and the median progress free survival (PFS) was 10.2 months (95% CI: 7.8-12.6). The 1year OS and PFS were 65% (95% CI: 0.479-0.864) and 41% (95% CI: 0.234-0.656), respectively. The incidence of adverse reactions was 27/29 (93.1%), and the incidence of grade III/IV adverse reactions was 5/29 (17.2%).The combination of chemotherapy, regorafenib, and immune checkpoint inhibitors as a first-line treatment for patients with advanced BTC may has good antitumor efficacy without causing serious adverse reactions, and can significantly improve the long-term prognosis.